An update on the treatment of cutaneous tumours. (2nd November 2021) - Hollis, Anna
Abstract : Cutaneous tumours continue to present a significant clinical challenge in equine practice. There are a large number of treatment options and selecting the appropriate modality requires careful consideration of a number of factors. While sarcoids are the most commonly diagnosed cutaneous tumour, their clinical appearance can have considerable overlap with other types of lesion, so biopsy should be performed where the diagnosis is uncertain. New treatment options for sarcoids include electrosurgery, electrochemotherapy and novel intralesional treatments. Melanomas still have relatively limited treatment options beyond surgical resection, but there are now limited data to support the use of a xenogenic DNA vaccination protocol. Squamous cell carcinomas are generally best treated via surgical excision, but a novel intralesional treatment may prove to be a useful option for further treatment.